x(x-3)=x(x-5)+18

Simple and best practice solution for x(x-3)=x(x-5)+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x-3)=x(x-5)+18 equation:


Simplifying
x(x + -3) = x(x + -5) + 18

Reorder the terms:
x(-3 + x) = x(x + -5) + 18
(-3 * x + x * x) = x(x + -5) + 18
(-3x + x2) = x(x + -5) + 18

Reorder the terms:
-3x + x2 = x(-5 + x) + 18
-3x + x2 = (-5 * x + x * x) + 18
-3x + x2 = (-5x + x2) + 18

Reorder the terms:
-3x + x2 = 18 + -5x + x2

Add '-1x2' to each side of the equation.
-3x + x2 + -1x2 = 18 + -5x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
-3x + 0 = 18 + -5x + x2 + -1x2
-3x = 18 + -5x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
-3x = 18 + -5x + 0
-3x = 18 + -5x

Solving
-3x = 18 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-3x + 5x = 18 + -5x + 5x

Combine like terms: -3x + 5x = 2x
2x = 18 + -5x + 5x

Combine like terms: -5x + 5x = 0
2x = 18 + 0
2x = 18

Divide each side by '2'.
x = 9

Simplifying
x = 9

See similar equations:

| -(7x+10)=8x+5 | | 5(n+4)-(9n-3)=-5n | | 3x+4x+15=4x-9 | | 8s^2-50=0 | | (x-7)2=4 | | 4(90-x)=180-x | | 12c^2-17cd-5d^2=0 | | 5x-22=8 | | 27=3(2x+1) | | 8+6=2x | | M=nx | | 4x-30=x+15 | | 10r^3+44r^2-30r=0 | | 4x-7=-3x+14 | | 5+1.6x=1 | | 10u^2-29u+10=0 | | x+3y=-9 | | 3(9-x)=5+x | | 7x-4=3(3+x)-1 | | 11x-5(3x+2)=14x+62 | | -8x+4y=24 | | 4(x+2)=-2(x-1) | | 3x+18=0 | | 3(5c-1)-2=12c+4 | | -x-8=2x+7 | | 2x-16=6(x-2) | | 2x=5x+12 | | 18a=b | | 4x+14=7x-4 | | 4n+8=26-2n | | 44-12=4(x-7) | | 35+3y-5=12y-12-3y |

Equations solver categories